Using web-based resources in learning : factors that affect degree students' readiness / Peridah Bahari and Salina Hamed - Bahari, Peridah; Hamed, Salina (Institute of Research, Development and Commercialization (IRDC), 2007)
The widespread acceptance of Web Technology in our tertiary institutions has brought about changes in the style, quantity and variety ofresources that are made available to students. Fundamentally new learning environment is provided f or students. On the other hand, there is still question about student readiness in using the abundant resources made available to them on the Web. This study examines students' readiness in using web-based resources. Variables that were look ed into are demographic background, level of technology usage, level of computer resour ces usage and their perspective on technology. 294 qu estionnaires were distribut ed randomly to degr ee engineering students (electrical, mechanical and civil). Based on students' ability on using web-based resources, result obtainedfrom quantitative data showe d there was a significant difference between student from different semesters (F = 4.032, P = 0.000) and their accommodation (t =7.255 and p = 0.007). Results ofthe Pearson correlation analysis revealed that there was a fair degree ofrelationship between students' ability and students' attitude on web-based resources (r = 0.310, P = 0.000)